'History is Screaming at Us': Humanitarian interventionism and the popular geopolitics of the Bosnian war in Leigh Jackson and Peter Kosminsky's Warriors. (29th February 2012) - Harper, Stephen
The representation of the 1992–1995 Bosnian war in both news media and popular cultural forms has received remarkably little scholarly attention. Drawing upon the recent work of radical historians and critics, this article begins with a reassessment of the dominant western news media narrative of the Bosnian conflict. It then proceeds to consider some popular representations of the conflict, focusing on Leigh Jackson and Peter Kosminsky's unduly neglected BBC two-part television drama Warriors. By comparison with United States and United Kingdom news media coverage of the conflict and other popular screen representations of the Bosnian war, Warriors offers one of the most sensitive and sophisticated accounts of the conflict. Nevertheless, the drama reproduces many of the fundamental western news media biases and implicitly endorses the discourse of humanitarian interventionism that has been used, particularly since the 1990s, to justify western military imperialism. That Kosminsky, who is known for making dramas that question dominant political paradigms, should have adopted an interventionist line in Warriors may suggest something of the potency and reach of western news media propaganda throughout the 1990s on behalf of what Noam Chomsky has called 'humanitarian imperialism'.